Жанрова специфіка літературного щоденника - Матвєєва, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The author of the article restores the theoretical historiography of diary genre. She investigates the logic of diary representation in the literature of the end of the XIX – the beginning of the XX century. The researcher proves that the specific features of genre determination is explained by the change of dominants: from documentation to literariness.